Morphometric variation among three local mangrove clam species of Corbiculidae - Idris, Mohd Hanafi; Kamal, Abu Hena Mustafa; Wong, Sing King (Prince of Songkla University, 2015)
Three common species of Corbiculidae (Polymesda erosa, P. bengalensis and P. expansa) can be found inhabiting the mangrove areas in Southeast Asia. The morphometric variations of three species were examined based on 15 morphometric characters. A total of 16 populations from six localities were analyzed in the present study. Analysis of variance had revealed significant differences (P<0.05) for LCT/SL and VPM/SL for proportion ratio on morphometric variables among species. Cluster analysis for these populations formed two groups at 70% of similarity. Morphometric characteristics, such as LCT and VPM, of Corbiculidae are proposed to differentiate these three species.